The Psychological Application of Curriculum Ideology and Politics - Ma, Yonghua; Gao, Jiong; Li, Yuling (Journal of Educational Research and Policies, 2025)
In recent years, due to an excessive emphasis on intellectual and knowledge-based education, other aspects of quality education have been relatively neglected. As a result, children’s psychological maturity and the development of their sense of social responsibility have been significantly delayed. Many college students feel that life lacks meaning. The Ministry of Education has successively proposed the requirements of ‘Three-Comprehensive Education’ and ‘curriculum ideology and politics’, aiming to return education to its fundamental purpose of nurturing individuals. This article approaches the issue from a psychological perspective, suggesting managing first impressions and utilizing effects such as the exposure effect, proximity effect, similarity effect, and Franklin effect to establish good relationships with students, thereby achieving better outcomes in ideological and political theory courses.